Accounting conservatism: A literature review - Ngo , Nhat Phuong Diem (Journal of Finance - Marketing Research, 2025)
Accounting conservatism reduces information imbalances in the accounting information system between people within the unit and information users outside the unit, reducing the ability to manage key custom reporting accounts (LaFond & Watts, 2008) and is a key determinant of financial reporting quality (DeFond & Zhang, 2014). Meanwhile, globalization and the internationalization of capital markets require very high transparency, timely response to financial reports, and the quality of main financial reports. Therefore, this study was conducted to provide an overview of prudential accounting in terms of definition, classification of prudential accounting, measurement methods, and important factors affecting prudential accounting. The results of this study have provided the most general theoretical foundation for prudential accounting, which is the basis for future research on this issue and at the same time provides a theoretical foundation to support readers gaining a comprehensive view of prudential accounting as well as its role in financial reporting quality to build appropriate research directions in the future.